PENGARUH CURRENT RATIO (CR), DEBT TO EQUITY RATIO (DER), TOTAL ASSETS TURNOVER (TATO), RETURN ON EQUITY (ROE), EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM - Ari Anggraini, 15.05.52.0273; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2019)
This study aims examine Current Ratio (CR), Debt to Equity Ratio (DER), Total Assets Turnover (TATO), Return On Equity (ROE) and Earning Per Share (EPS) to stock prices. This research was conducted in Indonesia by using an analysis unit of manufacturing companies that had gone public. The population of this study is manufacturing companies listed on the Indonesian Stock Exchange (IDX). The sampling method uses a purpose sampling. Research period from 2015 to 2017 ang obtained as many as 295 companies. The data analysis technique used is multiple linear regression analysis. The results of the study show that Current Ratio (CR) and Total Assets Turnover (TATO) have no effect on stock prices. Return On Equity (ROE) and Earning Per Share (EPS) have a positive influence on stock prices. While Debt to Equity Ratio (DER) has a positive effect on stock prices.